Geminoid Studies Science and Technologies for Humanlike Teleoperated Androids - Ishiguro, Hiroshi; Dalla Libera, Fabio (Springer Nature Singapore : Imprint: Springer, 2018)
This book describes the teleoperated android Geminoid, which has a very humanlike appearance, movements, and perceptions, requiring unique developmental techniques. The book facilitates understanding of the framework of android science and how to use it in real human societies. Creating body parts of soft material by molding an existing person using a shape-memory form provides not only the humanlike texture of the body surface but also safe physical interaction, that is, humanlike interpersonal interaction between people and the android. The teleoperation also highlights novel effects in telecommunication. Operators of the Geminoid feel the robot's body as their own, and people encountering the teleoperated Geminoid perceive the robot's body as being possessed by the operator as well. Where does the feeling of human presence come from? Can we transfer or reproduce human presence by technology? Geminoid may help to answer these questions. .